2006
DOI: 10.1007/bf03215557
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic methanol reforming on Au/TiO2 for hydrogen production

Abstract: Several metals in the form of nanoparticles loaded on metal oxides exhibit activity for photocatalytic production of hydrogen from water (1-4). Among them, gold has received attention recently in pollution control and fuel cell applications (5,6), but has received very little attention with regard to photocatalysis.The activity of gold loaded on metal oxides depends on many factors such the type of support material, the preparation method and the calcination temperature. This group has carried out a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…They reported ca. 135 μL/g cat min H 2 productivity, more than three times higher value than in liquid phase photoreforming [161].…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 88%
“…They reported ca. 135 μL/g cat min H 2 productivity, more than three times higher value than in liquid phase photoreforming [161].…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 88%
“…However, if operating as a window, obviously it would not be achieving its maximum potential since it needs to transmit a large proportion of the light. Further, in separate experiments we have found that maximum hydrogen production is only achieved when a layer *0.2 mm thick [34] is applied to the glass, which then absorbs/scatters most of the light. The gas produced from the panel passes through to a storage device which could either be batch storage or could be directly connected to the cooker.…”
Section: So What? the Photocatalytic Windowmentioning
confidence: 90%
“…10(a)) and 80:20 ( Fig. 10(b) [26][27][28][29][30][31][32]35]. At both ethanol concentrations, the 0.5 wt.% Au/TiNTx photocatalysts displayed excellent stability during the tests, as evidenced by the linearity of the H 2 production plots with UV irradiation time.…”
Section: Au/h 2 Ti 3 O 7 Au/tint350 Au/tint425mentioning
confidence: 87%
“…We are currently conducting detailed GC analyses of the other reaction products formed during Au/TiO 2 photo-excitation in the different alcoholwater mixtures, with the aim of better understanding the alcohol photo-oxidation pathway and role in promoting H 2 production. This will also allow the relative contributions of alcohol photoreforming and water-splitting to the observed H 2 yields to be determined, and meaningful comparisons to be drawn with prior related studies on the Pd/TiO 2 system [26][27][28][29][30][31][32]. Further photocatalytic tests are also being conducted under visible and full solar excitation, to determine the extent to which the plasmonic effect [35,[46][47][48] can enhance H 2 production rates.…”
Section: Au/h 2 Ti 3 O 7 Au/tint350 Au/tint425mentioning
confidence: 96%
See 1 more Smart Citation